Establishing an objective decision criterion for intraocular lens exchange due to homogeneous calcification: a prospective clinical analysis - Yildirim, Timur Mert; Łabuz, Grzegorz; Henningsen, Nikola; Son, Hyeck Soo; Augustin, Victor A.; Britz, Leoni; Chychko, Lizaveta; Khoramnia, Ramin; Auffarth, Gerd U. (Eye and Vision, 2024)
Homogeneous intraocular lens (IOL) calcification deteriorates patient’s visual quality. There is a lack of functional and patient-reported data on patients with this material change undergoing IOL exchange surgery. The aim of this study was to evaluate subjective and objective outcomes following IOL exchange due to homogeneous IOL calcification to improve evidence-based patient counseling. In this prospective, non-interventional, clinical study, 53 eyes of 42 patients with homogeneous IOL calcification were included. IOL exchange was performed in 30 out of 53 eyes. Subjective symptoms using a quality-of-life questionnaire (Catquest-9SF), photic phenomena, corrected distance visual acuity (CDVA), straylight (C-Quant, Oculus, Wezlar, Germany) and contrast sensitivity with and without glare (CSV-1000, VectorVision, Houston, USA) were assessed before (T0) and at 3 to 12 months after IOL exchange (T1). Preoperative CDVA and straylight did not correlate. Average halo and glare size and intensity decreased and Catquest-9SF items improved. The CDVA rose significantly from 0.16 ± 0.13 to 0.05 ± 0.10 logMAR, and contrast sensitivity increased with and without glare. The straylight value decreased statistically and clinically significant from 2.32 ± 0.34 to 1.23 ± 0.33 log(s). Homogeneous IOL calcification is not always associated with a pronounced reduction in visual acuity. In most cases, IOL exchange still reduces subjective complaints and improves quality of vision of affected patients. Visual acuity should not be the sole functional parameter in assessing patients with homogeneous IOL calcification as intraocular straylight and contrast sensitivity can better objectify patients’ visual impairment. We recommend a straylight value above 1.56 log(s) as a cut-off when deciding on an IOL exchange surgery.
Gesehen am 06.06.2026